2009
DOI: 10.3923/ajbkr.2010.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Characterization of a New Local Keratinase Producing Pseudomomanas sp., MS21

Abstract: This study aimed to isolate and identify a new local bacterial strain, able to completely degrade keratin-rich wastes into soluble and useful materials which can be used in many proposes. Bacterial keratinases are of particular interest because of their action on insoluble keratin substrates and generally on a broad range of protein substrates. These enzymes have been studied for de-hairing processes in the leather industry and hydrolysis of feather and keratin. Samples from poultry industry wastes, soil, wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The optimum temperature for keratinase activity was determined at different incubation temperatures between 0 and 100°C [13]. + were tested.…”
Section: Effect Of Ph and Temperature On Keratinase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum temperature for keratinase activity was determined at different incubation temperatures between 0 and 100°C [13]. + were tested.…”
Section: Effect Of Ph and Temperature On Keratinase Activitymentioning
confidence: 99%
“…Finally, the feathers were washed several times with tap water to eliminate the solvent residual, dried for 3 days at 50°C and ground using an electrical blender. The ground keratin was used for further studies [13].…”
Section: Preparation Of Native Chicken Feathermentioning
confidence: 99%
“…In this study, we aimed at isolation and molecular identification of bacterial strains from sludge samples collected from Peyposht and Qeshm, which have high quantities of keratin-rich waste. In a study by Tork et al, 7 of 23 bacterial isolates with bright halos on skim milk agar were identified as keratinase producer (15). A study by Sangali and Brandli reported the keratinolytic activity of Vibrio sp.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA was used as a template for PCR amplification of the 16S rRNA gene using forward primer 5'-AGTTTGATCATGGTCAG-3' and reverse primer 5' GGTTACCTTGTTACGACT 3' (Tork, Aly, & Nawar, 2010). The PCR product of each of the tested isolates was purified and sequenced.…”
Section: Molecular Identification Of Isolated Keratin Degrading Alkalmentioning
confidence: 99%